Ferroptosis-related ceRNA axis regulates the apoptosis and proliferation of uveal melanoma cells through MAPRE2 - Hai-Bo Wang; Li Dong; He-Yan Li; Xin Liu; Fan Zhang; Lin-Hui Yuan; Wen-Bin Wei (Functional & Integrative Genomics, 2026)

Single-cell RNA sequencing revealed changes in the tumor microenvironment induced by radiotherapy for cervical cancer and the molecular mechanism of mast cells in immunosuppression - Lujiadai Xue; Linzhi Gao; Shimin Zhou; Chaofan Yan; Xian Zhang; Wei Lin; Hu Li; Yuan Shen; Xiaoyu Wang (Functional & Integrative Genomics, 2025)

Heterogeneity analysis and prognostic model construction of HPV negative oral squamous cell carcinoma T cells using ScRNA-seq and bulk-RNA analysis - Chunyan Li; Zengbo Lv; Chongxin Li; Shixuan Yang; Feineng Liu; Tengfei Zhang; Lin Wang; Wen Zhang; Ruoyu Deng; Guoyu Xu; Huan Luo; Yinhong Zhao; et al. (Functional & Integrative Genomics, 2025)

Transcription factor MAZ activates the transcription of hypomethylated TYMP in ccRCC - Yihan Dong; Xinyu Liu; Jiaxin Li; Tianyu Lin; Rui Wang; Huamao Jiang; Yong Wang; Dan Yue (Functional & Integrative Genomics, 2025)

Long noncoding RNA LINC00482 silencing sensitizes non-small cell lung cancer cells to cisplatin by downregulating CLASRP via E2F1 - Yanming Lin; Jinmei Li; Shujun Li; Yuting Chen; Yiping Luo; Yongcun Wang; Zhixiong Yang (Functional & Integrative Genomics, 2023)

Integrated metabolomics and transcriptomics analyses reveal the key genes regulating differential metabolites of longissimus dorsi muscle in castrated South Sichuan black goats (Capra hircus) - Nanchi Zhang; Feng Xu; Li Wang; Quzhe Emu; Yong Wei; Lin Zhang; Yuan Xu; Jingsheng Fan; Yan Sun; Shuobu Shama; Hongyan Zhou; Chunmei Li; et al. (Functional & Integrative Genomics, 2023)

Pan-cancer evidence of prognosis, immune infiltration, and immunotherapy efficacy for annexin family using multi-omics data - Chong Shen; Siyang Zhang; Zhe Zhang; Shaobo Yang; Yu Zhang; Yuda Lin; Chong Fu; Zhi Li; Zhouliang Wu; Zejin Wang; Zhuolun Li; Jian Guo; et al. (Functional & Integrative Genomics, 2023)

Transcriptome analysis reveals the regulatory effects of Bacillus amyloliquefaciens and Bacillus pumilus on immune and digestive related genes in the spleen of weanling black goats - Nanchi Zhang; Juan Li; Li Wang; Yong Wei; Quzhe Emu; Feng Xu; Lin Zhang (Functional & Integrative Genomics, 2023)

Construction and validation of a bladder cancer risk model based on autophagy-related genes - Chong Shen; Yan Yan; Shaobo Yang; Zejin Wang; Zhouliang Wu; Zhi Li; Zhe Zhang; Yuda Lin; Peng Li; Hailong Hu (Functional & Integrative Genomics, 2023)

Girdin acts as an oncogene in gastric cancer by regulating AKT/GSK3β/β-catenin signaling - Yun Wang; Qiang Fu; Yun-jian Tao; Sheng-nan Ying; Heng-gao Zhong; Yue Zhu; Xiao-han Qian; Lin Miao; Li-hua Yang (Functional & Integrative Genomics, 2023)
ThE present work focused on exploring Girdin expression within gastric cancer (GC), examining the effect of Girdin on the cell phenotype of GC, and clarifying the underlying mechanisms. Girdin expression in GC samples was identified by immunohistochemistry (IHC) and quantitative real-time PCR (qRT-PCR) assays. Girdin-targeting siRNAs were transfected into GC cells; later, we examined GC cell proliferation, migration, invasion, and apoptosis, respectively. Additionally, the protein expression was examined through Western blotting assay. Moreover, the tumor implantation experiment was conducted for examining Girdin knockdown in vivo. The results showed that Girdin expression elevated within GC samples, which was associated with the dismal prognostic outcome. Girdin knockdown suppressed GC cell proliferation, migration, and invasion, and enhanced apoptosis and cell cycle arrest. Girdin promoted the phosphorylation of AKT, GSK3β, and β-catenin. Moreover, Girdin inhibited the phosphorylation of β-catenin. Girdin suppressed cell apoptosis and stimulated cell migration and invasion, while AKT inhibitor (MK2206) treatment reversed the effect of Girdin overexpression, and GSK3β inhibitor (CHIR99021) treatment enhanced the effect of Girdin overexpression on GC cells. Besides, Girdin delayed tumor growth in vivo. In conclusion, Girdin was abnormally expressed in GC samples, which promoted the development of GC by regulating AKT/GSK3β/β-catenin signaling.

Development of mitochondrial simple sequence repeat markers to simultaneously distinguish cytoplasmic male sterile sources in cotton - Yongqi Li; Meng Zhang; Kashif Shahzad; Yang Han; Xuexian Zhang; Liping Guo; Tingxiang Qi; Huini Tang; Hailin Wang; Xiuqin Qiao; Juanjuan Feng; Zhongxu Lin; et al. (Functional & Integrative Genomics, 2023)

CircPVT1 facilitates the progression of oral squamous cell carcinoma by regulating miR-143-3p/SLC7A11 axis through MAPK signaling pathway - Shiliang Wang; Wenlu Li; Long Yang; Jianqiao Yuan; Lin Wang; Na Li; Hongyu Zhao (Functional & Integrative Genomics, 2022)

Association of DNA methylation and transcriptome reveals epigenetic etiology of heart failure - Zhongxiao Lin; Jishuo Chang; Xinzhi Li; Jianglin Wang; Xiaodan Wu; Xiaoyan Liu; YiZhun Zhu; Xi-Yong Yu (Functional & Integrative Genomics, 2022)

Identification and bioinformatics analysis of differentially expressed milk exosomal microRNAs in milk exosomes of heat-stressed Holstein cows - Yue Wang; Jian Fang; Han-Fang Zeng; Ji-Feng Zhong; Hui-Xia Li; Kun-Lin Chen (Functional & Integrative Genomics, 2022)

ARRDC3 polymorphisms may affect the risk of glioma in Chinese Han - Nan Li; Hangyu Shi; Pengfei Hou; Lu Gao; Yongqiang Shi; Weiyang Mi; Gang Zhang; Ning Wang; Wei Dai; Lin Wei; Tianbo Jin; Yongzhi Shi; et al. (Functional & Integrative Genomics, 2022)

Untargeted metabolomic analysis of urine samples for diagnosis of inherited metabolic disorders - Hao Liu; Jiang Zhu; Qiu Li; Dongjuan Wang; Kexing Wan; Zhaojian Yuan; Juan Zhang; Lin Zou; Xiaoyan He; Jingkun Miao (Functional & Integrative Genomics, 2021)

Gene expression profiles of HTR8-S/Vneo cells after changes in ABCA1 expression - Chengmao Xie; Xiaohui Cai; Xiaoju Wang; Li Lin; Yan Long; Xin Cui (Functional & Integrative Genomics, 2018)

Identification of two novel chicken GPR133 variants and their expression in different tissues - Kai Tian; Qihai Xiao; Xueyou Zhang; Xi Lan; Xiaoling Zhao; Yan Wang; Diyan Li; Huadong Yin; Lin Ye; Qing Zhu (Functional & Integrative Genomics, 2017)

Migration of endophytic diazotroph Azorhizobium caulinodans ORS571 inside wheat (Triticum aestivum L) and its effect on microRNAs - Li Qiu; Qiang Li; Junbiao Zhang; Yongchao Chen; Xiaojun Lin; Chao Sun; Weiling Wang; Huawei Liu; Baohong Zhang (Functional & Integrative Genomics, 2017)

Type 3 iodothyronine deiodinase in neonatal goats: molecular cloning, expression, localization, and methylation signature - Tao Zhong; Peng-Fei Jin; Wei Zhao; Lin-Jie Wang; Li Li; Hong-Ping Zhang (Functional & Integrative Genomics, 2016)

GmPGIP3 enhanced resistance to both take-all and common root rot diseases in transgenic wheat - Aiyun Wang; Xuening Wei; Wei Rong; Liang Dang; Li-Pu Du; Lin Qi; Hui-Jun Xu; Yanjun Shao; Zengyan Zhang (Functional & Integrative Genomics, 2015)

Transcript suppression of TaGW2 increased grain width and weight in bread wheat - Yantao Hong; Longfei Chen; Li-pu Du; Zhenqi Su; Jinfen Wang; Xingguo Ye; Lin Qi; Zengyan Zhang (Functional & Integrative Genomics, 2014)